Individual'nost' i effektivny arsenal tekhniki v sportivnoi bor'be - Okhotin, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
On the problem and importance of individual training in the long course training process in combat sports for the best realization of the individual potential in competition. In combat sports this problem is especially important because a fight can be carried out (and won or lost) in different ways.